«Засмотрите и зацените»: продуктивность приставки за- в современном русском языке(“Zasmotrite i zacenite”: Productivity of the Prefix ZA- in Modern Russian) - Sokolova, Svetlana (Poljarnyj vestnik, 2009)
This paper discusses the main tendencies in which the Russian prefix ZA- appears to be productive. Since the two major instantiations of its productivity, i.e. its inchoative use and the ability to form perfective counterparts of bi-aspectual verbs, are rather well described in the literature we place our focus on the usage of ZA- in modern slang. We analyze those cases where the prefix ZA- seems to replace other prefixes in aspectual pairs which are traditionally used and listed in dictionaries. Based on data from websites, the paper offers a detailed analysis of two groups of verbs: verbs like za-cenit’ ‘to estimate, check something out’ (instead of o-cenit’) in youth slang and verbs like za-modelirovat’ ’to model’ (instead of s-modelirovat’) in professional slang. Both groups of verbs show regularity and extensibility of the prefix ZA- and reflect the meanings of ’fixation’ and ’excessiveness’, which appear to be communicatively important for the prefx ZA-. We believe that by analyzing the productivity of a prefix and profiling its communicatively important meanings we may contribute to the description of its semantic network.